The Impact Of Audit Committe Characteristics On Audit Quality - Paradisa Sukma; Yustrida Bernawati (Jurnal Akuntansi, 2019)
This research was conducted to investigate the effect of audit committee characteristics on audit quality. The characteristics of the audit committee used in this study are the number of audit committees, number of audit committee meetings, audit committee education background, and audit committee experience while audit quality is measured using audit fees. This study uses manufacturing companies listed on the Indonesia Stock Exchange in 2016 - 2018 with 70 observation data and uses OLS regression. The results of this study indicate all four Audit Characteristics, only size and experience significantly influence audit quality. While audit meetings and education do not significantly affect audit quality. Likewise with the education that can not ensure the capabilities possessed by members of the audit committee. Overall, the effectiveness of the audit committee has no significant effect on audit quality.